Molecular basis of alternating access membrane transport by the sodium-hydantoin transporter Mhp1. - Shimamura, T; Weyand, S; Beckstein, O; Rutherford, N; Hadden, J; Sharples, D; Sansom, MS; Iwata, S; Henderson, P; Cameron, A (2010)
The structure of the sodium-benzylhydantoin transport protein Mhp1 from Microbacterium liquefaciens comprises a five-helix inverted repeat, which is widespread among secondary transporters. Here, we report the crystal structure of an inward-facing conformation of Mhp1 at 3.8 angstroms resolution, complementing its previously described structures in outward-facing and occluded states. From analyses of the three structures and molecular dynamics simulations, we propose a mechanism for the transport cycle in Mhp1. Switching from the outward- to the inward-facing state, to effect the inward release of sodium and benzylhydantoin, is primarily achieved by a rigid body movement of transmembrane helices 3, 4, 8, and 9 relative to the rest of the protein. This forms the basis of an alternating access mechanism applicable to many transporters of this emerging superfamily.